Biomass Fractionation and Lignin Fractionation towards Lignin Valorization - Xu, Jiayun; Li, Chenyu; Dai, Lin; Xu, Chunlin; Zhong, Yongda; Yu, Faxin; Si, Chuanling (ChemSusChem, 2020)
Lignin, as the most abundant aromatic biopolymer in nature, has attracted great attention due to the complexity and richness of its functional groups for value‐added applications. The yield of production of lignin and the reactivity of prepared lignin are very important to guarantee the study and development of lignin‐based chemicals and materials. Various fractionation techniques have been developed to obtain high yield and relatively high‐purity lignin as well as carbohydrates (hemicelluloses and celluloses) and to reduce the condensed and degraded nature of conventional biorefinery lignin. Herein, novel and efficient biomass fractionation and lignin fractionation towards lignin valorization are summarized and discussed. How to fractionate efficiently: Efficient fractionation strategies for lignin are the key and basis for the subsequent transformation into value‐added products. Herein, efficient approaches of lignin fractionation towards lignin valorization are reviewed.